In Vivo Confocal Microscopy of Cornea in Patients with Terrien’s Marginal Corneal Degeneration - Ting Chen; Qiangxiang Li; Xiangbo Tang; Min Liao; Hua Wang (Journal of Ophthalmology)
This study was aimed at observing the morphological changes of the cornea with ocular in vivo confocal microscopy (IVCM) in patients with Terrien’s marginal degeneration (TMD). Ten patients (20 eyes) with TMD treated in the Department of Ophthalmology, Xiangya Hospital, and 10 healthy controls (20 eyes) were included in the current study. A detailed slit lamp microscopy, anterior segment photography, and corneal IVCM examination were performed for each eye. The density of central and marginal corneal epithelial cells, stromal cells, and subepithelial nerve fibers was compared between the two groups using the Wilcoxon rank sum test. Compared with the control group, the corneal epithelial and endothelial cells in the TMD group showed granular highly reflective substances and thinner subepithelial nerve fibers. The uneven dot-like highly reflective substances without cell structures appeared in the stromal layer of the cornea. The density of central and marginal corneal epithelial cells, stromal cells, and subepithelial nerve fibers was lower in the TMD group (p<0.05), and they were negatively correlated with severity of the disease (p<0.05). Our study demonstrated that the density of corneal epithelial cells, stromal cells, and sensory plexus nerve fibers was significantly reduced in the TMD group. The pathological changes were more obvious in the marginal cornea, and it is correlated with severity of the disease.